How Long Does It Take for Patients to Complete PROMIS Scores? An Assessment of PROMIS CAT Questionnaires Administered at an Ambulatory Sports Medicine Clinic. Issue 8 (9th August 2018) - Kadri, Omar; Jildeh, Toufic R.; Meldau, Jason E.; Blanchett, Jacob; Borowsky, Peter; Muh, Stephanie; Moutzouros, Vasilios; Makhni, Eric C.
Background: Challenges exist in routinely collecting patient-reported outcomes (PROs) from patients at a busy ambulatory clinic. A number of validated Patient-Reported Outcomes Measurement Information System (PROMIS) subdomains allow for efficient PRO administration. Purpose: To determine the time to completion (TTC) of 3 PROMIS computer adaptive test (CAT) scores. CAT questionnaires were administered at the ambulatory clinic with the following PROMIS subdomains: Pain Interference (PI), Depression, and Physical Function for lower extremity (PF) or for upper extremity (UE). The secondary purpose was to determine the influence of patient demographic factors on TTC. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Patients were recruited from 3 fellowship-trained upper extremity and sports medicine orthopaedic surgery clinics. PROMIS CAT questionnaires were administered to consecutive patients during the study period (July 2017–September 2017). The start and completion times of each CAT were recorded. The primary outcome of interest was TTC of the questionnaires. Patients were stratified into age quartiles to determine the impact of age on TTC. Patient demographic information, such as sex, race, and ethnicity, was determined retroactively. Results: A total of 1178 questionnaire sets consisting of 3658 individual PROMIS forms were analyzed. The mean TTC was 3.29 minutes for all 4 forms in aggregate, with PROMIS PI, PF, UE, and Depression taking on average 1.05, 0.74, 0.96, and 0.57 minutes to complete, respectively. Patients from the oldest age quartile (mean ± SD, 70.3 ± 7.5 years) had a statistically significant longer TTC as compared with the second quartile (41.2 ± 4.7 years) (3.70 vs 2.87 minutes; P < .05). Asian patients had the longest PROMIS PF TTC, while white patients completed PF with the shortest TTC (1.28 vs 0.68 minutes; P < .05). Patients of unstated ethnicity had a longer TTC for PF as compared with their Hispanic/Latino and non-Hispanic/Latino counterparts (0.91 vs 0.30 and 0.70 minutes; P < .05). Conclusion: PROMIS CAT forms are efficient tools for collecting patient-reported outcomes in the ambulatory orthopaedic surgery clinic. Older patients, Asian patients, and patients of unstated ethnicity took longer to complete the forms.